1984
DOI: 10.1071/ch9841825
|View full text |Cite
|
Sign up to set email alerts
|

Applications of molybdenum-95 N.M.R. spectroscopy. X. Polyoxomolybdates

Abstract: An initial survey of the 95Mo n.m.r. properties of a range of 12 polyoxomolybdates is presented. The species resonate in the range - 18 to + 140 ppm. The observed line widths generally exceed 100 Hz for six-coordinate molybdenum sites of low symmetry, but can be narrow (< 20 Hz at 20�) for four-coordinate sites. Aqueous solutions of [Mo7O24]6- at pH 6.1 exhibit exchange between Mo- and Mo7-based species. Solutions of α-[Mo8O26]4- in MeCN feature a single narrow resonance (δ16, Wh/2 23 Hz at 20�) assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 0 publications
3
42
0
Order By: Relevance
“…1a, spectrum 4) and lines that are typical of β-Mo 8 O 26 4- [8], but slightly shifted (Fig. 1a, spectrum 3).…”
Section: Resultsmentioning
confidence: 91%
“…1a, spectrum 4) and lines that are typical of β-Mo 8 O 26 4- [8], but slightly shifted (Fig. 1a, spectrum 3).…”
Section: Resultsmentioning
confidence: 91%
“…6,[8][9][10] The 95 Mo and 183 W signals of the most important polyoxometalates have previously been assigned, in particular for M 7 O 24 6− (M = W, Mo), the predominant species at acidic pH values. [75][76][77] Polyoxotungstates give rise to sharp 183 W signals, but 95 Mo signals of polyoxomolybdates are generally broadened, which makes it difficult to detect and, in particular, to quantify them in solution.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of Na 6 TeMo 6 O 24 ·xH 2 O was carried out according to the method of Filowitz et al [17] The product composition and its purity were confirmed by elemental analysis and the 17 O and 95 Mo NMR spectra. [17,18] NMR spectra were measured with a Bruker Avance-400 spectrometer, at the natural content of 125 Te, 17 O, and 95 Mo (≈ 7, 0.04, and 16 %, respectively). The 125 Te chemical shifts (δ) given relative to Me 2 Te were determined by using telluric acid aqueous solution as a secondary external standard (δ = 707 ppm).…”
Section: Methodsmentioning
confidence: 99%
“…With this aim in mind, we have applied multinuclear NMR spectroscopy, as it is the most informative technique for studying speciation of POMs in solutions. [16][17][18] …”
Section: Introductionmentioning
confidence: 99%